Enhancing biomass and lipid yield of microalga Scenedesmus obliquus by the periodic direct current. (August 2022) - He, Zhongqi; Jin, Wenbiao; Zhou, Xu; Han, Wei; Gao, Shuhong; Chen, Chuan; Chen, Yidi; Yin, Shiyu; Che, Lin; Jiang, Guangming
Abstract: Nowadays, the disposal of municipal wastewater by microalgae while extracting microalgal high-value by-products has become an emerging trend. In this research, direct current electrochemical treatment was used to improve microalgae biomass production and wastewater treatment effect simultaneously. After electrochemical treatment, the cell number, biomass, chlorophyll- a content and lipid content of Scenedesmus obliquus cultivated in BG11 medium were significantly increased respectively by 13.1%, 32%, 9.7% and 30.1% at the 1.0 A/m 2 direct current density. When Scenedesmus obliquus was cultured in real wastewater with electrochemical treatment at the 2.0 A/m 2 direct current density, the biomass and lipid yield increased by 30.1% and 23.5%, respectively, while the removal of TP, ammonia and TN was also obviously accelerated. Therefore, the electrochemical cultivation of Scenedesmus obliquus offers good prospects for wastewater treatment and resource recycling. Graphical abstract: Unlabelled Image